KOORDINASI DINAS PENDAPATAN DAERAH KOTA PEKANBARU DAN DINAS TATA RUANG DAN BANGUNAN KOTA PEKANBARU DALAM MENANGANI PAJAK REKLAME DI KOTA PEKANBARU - Ni Enda Wijayati Kusuma Wardhani; Chalid Sahuri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Advertisement tax is a big contributor to revenue . Advertisement tax revenue Pekanbaru often there is a discrepancy between the initial target with the realization . Realization is always lower than the initial target . This can be due to several things . Several related agencies responsible for this as the Regional Revenue Office Pekanbaru and Department of Spatial Planning and Building Pekanbaru. Regional Revenue Office Pekanbaru City billboard contribute to income funds , while the Department of Spatial Planning and Building Pekanbaru City is responsible for the licensing and operation of buildings billboards have building permit . The purpose of this study was to determine how the coordination between the relevant agencies in handling the advertisement tax and to determine the factors that influence the coordination between the relevant agencies . This research was conducted in the city of Pekanbaru precisely in Pekanbaru City Regional Revenue Office and the Department of Spatial Planning and Building Pekanbaru using qualitative descriptive method , with the technique of collecting data through observation and interviews . This research was conducted by using the theory according to Fayol , Koontz and O'Donnell are communication , cooperation , sharing of tasks and meetings meetings Results from this study indeed there is coordination of relevant agencies , namely the Regional Revenue Office Pekanbaru and Department of Spatial Planning and Building Pekanbaru City but has not done well . This is evidenced by their coordination after a foul on billboards building , should be coordination among related agencies can be done at this stage of the implementation and supervision of the building so that the advertisement has not been a violation of the impact on the building billboard advertising tax revenue .Key word: Coordination , advertisement tax , Licensing